دراسة لتطور الجباية العادية في الجزائر خلال الفترة (2017-2001) - بن خزناجي, أمينة (جامعة الوادي - University of Eloued, 2018)
يتمحور الهدف من هذا البحث حول معرفة مدى استقرار إيرادات الجباية العادية في الجزائر للفترة الممتدة بين 2001 و2017، إضافة إلى معرفة مدى مساهمتها في الإيرادات العامة للميزانية وفي تغطية النفقات العامة للدولة. كما اشتمل هذا البحث على جانبين أساسيين: الأول يتمثل في الإطار النظري للميزانية العامة والجباية العادية، أما الثاني فهو عبارة عن دراسة تحليلية لتطور هيكل الجباية العادية وكذلك تطور نسبة مساهمتها في الإيرادات العامة وتغطيتها للإنفاق الحكومي، توصلنا من خلالها لمجموعة هامة من النتائج أبرزها المساهمة الضئيلة للجباية العادية في تمويل الميزانية وكذلك تذبذب حصيلة الجباية العادية رغم تطورها الملحوظ خلال الفترة (2001-2017). The purpose of this research is to determine the extent of the stability of the ordinary fiscality revenues in Algeria between 2001-2017, in addition to know their contribution in the general budget revenues and in covering the public expenditure of the State. This research includes two main parts: the first is the theoretical framework of the general budget and the ordinary fiscality, the second is an analytical study of the evolution of the ordinary fiscality structure and the development of its contribution in the public revenues and its coverage of the government expenditure. Through this study we obtained a set of results, the most important is the small contribution of the ordinary fiscality in financing the budget, also, the fluctuation of the ordinary fiscality revenues between (2010-2007)
Study of the development of the ordinary taxation in Alegria during the preriod (2001-2017)
مقال
Keywords: الجباية العادية، تحليل، الجزائر; ordinary fiscality, analysis, Algeria.